The Investigation of the Application of Multimedia Health Education on the Knowledge of Activity: The Case of Knee Replacement Operation and Postoperative Wound - Huang, Yu-Ju; Hsieh, Tsung-Yu; Chuang, Ya-We (Asian Journal of Economic Modelling, 2017)
Since Taiwan’s society structure has come to an aged society, knee arthroplasty surgery has become one of the most common operations in this society. Under the National Health Insurance and its case payment system, the patients are asked to leave the hospital earlier which the hospitalization period and the relevant education for recovery after the operation are both shortened that has impacted patients’ body movements after the operation. The cooperation between the patient and his/her family members and the provision of health care information from the medical personnel become Ministry of Health and Welfare’s first priority to pursue in order to maintain patient’s health and wellbeing (Ministry of Health and Welfare, 2014). The objects of the research are patients in the National Cheng Kung University Hospital Dou-Liou Branch- the fifth room that contained the most Osteoarthritis patients and had experienced the total knee arthroplasty surgery. The characteristics of such patients including: the low educational level of the patient him/herself or the caregiver, less family company, unqualified home care environment that result from the insufficient health care education and the different level of after-operation health care understanding which lead to the negative effect on patients’ recovery from time to time. The research is based on the characteristics of such patients in Yun Lin and it is expected the analysis on such characteristics and the application of diversify health care tutorial to increase the effect after the knee replacement operation. Furthermore, it could effectively and practically prevent from the time consuming situation occurs between the communication of patients and medical personal which the health care satisfaction and quality could be effectively increase. And academically, it is expected to provide scholar in relevant research field a reference for the positive effects on diversify health care.